The Socialization of Multicultural Values in Early Childhood for Kindergarten (TK) and Raudatul Atfal (RA) Teachers in Pontianak - Yapandi Yapandi (Universitas Tanjungpura, 2018)
Multicultural education for early childhood is very urgent to be encouraged as a foundation for the development of a more open, tolerant and democratic Indonesian society. Early age is an important phase in child growth and development. The process of forming identity and character starts from early childhood. For this reason, equality values that do not consider themselves and their groups as superior to themselves and other groups are very important to be instilled in children as early as possible. This is important because on the one hand diversity in Indonesia is a reality that children will experience when they grow and develop, but on the other hand there are many phenomena that occur, namely blasphemy cases, social, religious and religious complexes that teach intolerance, in West Kalimantan from 1962-1999 there were 12 social, religious and ethnic conflicts. It is an important aspect of multicultural values in early childhood in this study.